(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the supportive effects of Kien toan ap Dai Hong Phuc in controlling blood pressure and serum lipids levels in hypertensive patients with dyslipidemia. Materials and methods: A controlled clinical intervention was conducted on 60 patients diagnosed with stage 1 or stage 2 hypertension accompanied by dyslipidemia, treated at Hanoi Traditional Medicine General Hospital from November 2024 to October 2025. Patients were categorized into two comparable groups: the control group was treated with standard therapy, while the study group was treated standard therapy combined with Kien toan ap Dai Hong Phuc. Results: In the study group, the mean systolic blood pressure decreased significantly from 156.87 ± 8.48 mmHg to 130.40 ± 6.55 mmHg; mean diastolic blood pressure decreased from 86.63 ± 8.23 mmHg to 70.00 ± 5.77 mmHg; and mean arterial pressure decreased from 110.03 ± 7.89 mmHg to 91.60 ± 5.48 mmHg, showing a statistically significant difference compared to the control group (p < 0.05). Serum lipids levels of the study group showed a tendency of better improvement compared to the control group; however, these differences were not statistically significant (p > 0.05). Conclusion: Kien toan ap Dai Hong Phuc poses supportive efficacy in lowering blood pressure and shows a tendency in improving lipids levels in studied hypertensive patients with dyslipidemia